Hubungan antara Penggunaan Media Sosial Twitter dengan Keterbukaan Diri Mahasiswa - Dhita Fahira; Neni Yulianita (UNISBA Press, 2022)
Abstract. The development of technology and information has developed rapidly. The things that arise from its development have a considerable impact on life.Technological advances have also given birth to various forms of new media or can be called new media in establishing internet-based communications, computers, and various other forms of social networking. The development of technology and information has developed rapidly. The things that arise from its development have a considerable impact on life.Technological advances have also given birth to various forms of new media or can be called new media in establishing internet-based communications, computers, and various other forms of social networking. Twitter has features that can appeal to its users, such as features for mentions, direct messages, latest news, trending and others. The average content on Twitter tends to upload users sharing their stories, activities, and personal opinions with selected people or followers of these users. With the social media twitter allows its users to be more open about themselves. Therefore, the researcher was interested in conducting a research entitled,